Faculty from Marginalized Groups in the Health and Social Service Professions: Challenging “Expected Academic” Identity and Roles - Pride, Tara; Sibbald, Kaitlin; MacLeod, Anna; Martin, Debbie; Owen, Michelle (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2023)
Academics have historically been members of socially dominant groups—white, cisgender, heterosexual men, from middle- to upper-classes, who identify as able-bodied and able-minded. Members of other groups are often disadvantaged. In two larger studies, semi-structured interviews were conducted with professionals from marginalized groups. Here we explore the narratives of 16 participants who explicitly discussed their experiences in faculty positions within the health and social service professions. The expected academic roles of teacher, researcher, and colleague/administrator did not neatly fit for participants, clashing with the expectations they faced by virtue of their marginalized identities. Within the health and social service professions, the norms and expectations of the academy required marginalized faculty to make sacrifices of their time and sense of self to meet job demands. The effects of these role conflicts are pervasive, affecting many areas of academic work and beyond.